2016
DOI: 10.1515/forj-2016-0007
|View full text |Cite
|
Sign up to set email alerts
|

Species composition and diversity of non-forest woody vegetation along roads in the agricultural landscape

Abstract: Non-forest woody vegetation represents an important component of green infrastructure in the agricultural landscape, where natural and semi-natural forest cover has only a low land use proportion. This paper focuses on linear woody vegetation structures along roads in the agricultural landscape and analyses them in three study areas in the Nitra Region, Slovakia. We evaluate species composition and diversity, species occurrence frequency or spatial distribution, their structure according to relatively achievab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Beyond the knowledge gap, the determinant of methodological considerations (n = 16. 11%) seeks to describe the constraints and limitations in available evidence (e.g., on the multidimensional benefit of cultural heritage preservation) [67], data (e.g., available historical and projected climatic data) [74], methods, and tools and methodologies to improve the drought resilience of woody plant species [94]. Several publications mentioned the gap in the use of quantitative methods of understanding the interactions between land-use, -cover, and climatic changes [61,[95][96][97].…”
Section: Technical Barriersmentioning
confidence: 99%
“…Beyond the knowledge gap, the determinant of methodological considerations (n = 16. 11%) seeks to describe the constraints and limitations in available evidence (e.g., on the multidimensional benefit of cultural heritage preservation) [67], data (e.g., available historical and projected climatic data) [74], methods, and tools and methodologies to improve the drought resilience of woody plant species [94]. Several publications mentioned the gap in the use of quantitative methods of understanding the interactions between land-use, -cover, and climatic changes [61,[95][96][97].…”
Section: Technical Barriersmentioning
confidence: 99%
“…From the published sources, we have found that Europe was particularly attractive to American tree species, with Robinia pseudoacacia significantly dominating the habitats of NFWV in agricultural landscapes. For instance, Tóth et al (2016) have mapped and assessed three selected cadastral territories in the Nitra Region and derived a conclusion that Robinia pseudoacacia has the highest frequency factor among all identified predominant tree species in NFWV structures. In the European List of Invasive Plants, up to 7 woody plant species are in the category of invasive (Brundu and Richardson, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…In human settlement landscapes, non-forest woody vegetation represents an important component of green infrastructure in the agricultural areas, where natural and semi-natural forest cover has only a low land use proportion (Tóth et al, 2016). Urban afforestation produces a great enhancement in the flora of cities; but if improperly planted, they generate disturbances (de Oliveira et al, 2018).…”
Section: Discussionmentioning
confidence: 99%